1991
DOI: 10.1111/j.1365-246x.1991.tb01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave anisotropy across the geothermal field of Milos, Aegean volcanic arc

Abstract: S U M M A R YThe drilled geothermal reservoir of Milos island, Aegean sea (Greece) is densely sampled by seismic waves from local earthquakes occurring at depths of 4-6 km, recorded by numerous three-component seismographs. During the eight months of observation seismic activity on the island occurred in the form of a few swarms located in three different areas. The focal mechanisms of all earthquakes share an area of dilatational quadrants indicating a nearly vertical maximum compressive stress. This implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…From that research we note that the delay times can be highly variable, depending upon the geology conditions and the tectonic features of a given region. For instance, KANESHIMA (1990) reported delay times of up to 0.21 seconds for various regions in Japan; SACHPAZI and HIRN (1991) observed mean delay times of 0.05 seconds for a geothermal field in Greece; BIANCO et al (1996) In this study, it is found that regardless of the hypocenter location of the earthquakes, the observed delay times are between 0.0 and 0.6 seconds. The overall mean value of these measurements was found to be equal to 0.35 seconds.…”
Section: Delay Times Between Fast and Slow S Wavesmentioning
confidence: 62%
“…From that research we note that the delay times can be highly variable, depending upon the geology conditions and the tectonic features of a given region. For instance, KANESHIMA (1990) reported delay times of up to 0.21 seconds for various regions in Japan; SACHPAZI and HIRN (1991) observed mean delay times of 0.05 seconds for a geothermal field in Greece; BIANCO et al (1996) In this study, it is found that regardless of the hypocenter location of the earthquakes, the observed delay times are between 0.0 and 0.6 seconds. The overall mean value of these measurements was found to be equal to 0.35 seconds.…”
Section: Delay Times Between Fast and Slow S Wavesmentioning
confidence: 62%
“…Monitoring shear-wave splitting is thus an important means to determine the direction and evaluate the bulk density of subsurface fractures in hydrocarbon or geothermal reservoirs (Cliet et al, 1991;Mueller,1991;Sachpazi and Him, 1991;Sato et al, 1991;Crampin, 1993). In this paper, we report on the determination of fracture patterns and crack density in the Coso geothermal field, California, by shear-wave splitting inspection and analyses of a large number of microearthquake seismograms recorded by a downhole, three-component seismic network.…”
Section: Introductionmentioning
confidence: 98%
“…Until now VSPs have generally been used for these studies (Cliet et al, 199I;Lefeuvre et al, 1992). Anisotropy has also been observed and related to crack density and local stress field by using shear-wave splitting of shallow earthquake data in geothermal areas (Kaneshima et al, 1988; Sachpazi et al, 1991). In the present study, we propose to use the induced seismicity observed in the hydrocarbon field of Lacq (France) for estimating the mean characteristics of the anisotropy.…”
Section: Introductionmentioning
confidence: 94%